CORRECTIVE CONTENT OF SENSORY EDUCATION OF STUDENTS WITH MENTAL RETARDATION (Conferencea, 2024)
This article describes the correctional content of sensory education of students with mental retardation, its generalizing functions, the practical implementation of educational work in the auxiliary school, and the three components of the education, training and development plan.